2012
DOI: 10.4236/acs.2012.24040
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Learning of Climate Sensitivity I: Synthetic Observations

Abstract: The instrumental temperature records are affected by both external climate forcings—in particular, the increase of long-lived greenhouse gas emissions—and natural, internal variability. Estimates of the value of equilibrium climate sensitivity—the change in global-mean equilibrium near-surface temperature due to a doubling of the pre-industrial CO<sub>2</sub> concentration—and other climate parameters using these observational records are affected by the presence of the internal variability. A diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Its three uncertain parameters are climate sensitivity ( S ); ocean vertical diffusivity ( κ ), controlling the rate of heat ocean uptake and the climate response time; and the aerosol radiative forcing strength ( α ), expressed as a factor multiplying the historical or projected forcing time series. These three parameters are generally assumed in climate sensitivity studies to be the most dominant physical uncertainties in the global temperature response [ Forest et al , ; Knutti et al , ; Urban and Keller , ; Ring and Schlesinger , ]. In addition, the initial temperature ( T 0 ) and ocean heat anomalies ( H 0 ) at the beginning of the model integration (the year 1850), and the standard deviation ( σ ) and annual autocorrelation ( ρ ) of the data model residuals, are also treated as uncertain parameters to be estimated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its three uncertain parameters are climate sensitivity ( S ); ocean vertical diffusivity ( κ ), controlling the rate of heat ocean uptake and the climate response time; and the aerosol radiative forcing strength ( α ), expressed as a factor multiplying the historical or projected forcing time series. These three parameters are generally assumed in climate sensitivity studies to be the most dominant physical uncertainties in the global temperature response [ Forest et al , ; Knutti et al , ; Urban and Keller , ; Ring and Schlesinger , ]. In addition, the initial temperature ( T 0 ) and ocean heat anomalies ( H 0 ) at the beginning of the model integration (the year 1850), and the standard deviation ( σ ) and annual autocorrelation ( ρ ) of the data model residuals, are also treated as uncertain parameters to be estimated.…”
Section: Methodsmentioning
confidence: 99%
“…Ring and Schlesinger [] produced an estimate of joint climate parameter learning (climate sensitivity, ocean diffusivity, and aerosol forcing) using an EBM with upwelling diffusive ocean. It considers Bayesian learning from surface temperature and radiative imbalance from ocean heat uptake, using synthetic historical and future observations generated from the EBM and a singular spectrum analysis of historical climate variability.…”
Section: Introductionmentioning
confidence: 99%
“…Ring and Schlesinger 42 is a development from Ring et al 38 using a root-mean-square error method to estimate ECS, ocean heat diffusivity (K), and direct sulfate aerosol forcing (F SA ) parameters with an SCM. 42 Synthetic observations were employed to test a Bayesian estimation procedure to see if 'true' values of ECS, ocean diffusivity, and aerosol forcing could be determined. They found that ECS and K did converge given enough time but F SA was not found due to a low signal-to-noise ratio for the interhemispheric temperature difference used to constrain F SA .…”
Section: Shift From Prognostic To Diagnostic Modementioning
confidence: 99%
“…Bayesian estimation has also been applied in related studies. Ring and Schlesinger is a development from Ring et al using a root‐mean‐square error method to estimate ECS, ocean heat diffusivity (K), and direct sulfate aerosol forcing (F SA ) parameters with an SCM . Synthetic observations were employed to test a Bayesian estimation procedure to see if ‘true’ values of ECS, ocean diffusivity, and aerosol forcing could be determined.…”
Section: Shift From Prognostic To Diagnostic Modementioning
confidence: 99%